Meningkatkan Pemahaman Konsep Siswa Pada Materi Perubahan Wujud Zat Melalui Eksperimen IPA Pada Siswa Kelas VII MTs Al Mizan - Dahlia Dahlia; Samsul Bahri (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This research is motivated by the low conceptual understanding of students on the material of changes in the state of matter which is still often learned through verbal explanations and less involving direct scientific experience. The research gap lies in the still limited science experiment studies that verify the improvement of MTs students' conceptual understanding through a more careful pretest-posttest analysis. This study aims to analyze the effect of the implementation of science experiments on the conceptual understanding of grade VII students of MTs Al-Mizan on the material of changes in the state of matter. The study used a quantitative approach with a one-group pretest-posttest design. The research sample consisted of 16 students who participated in all series of learning activities, pretest, and posttest. The research instruments were in the form of a concept understanding test and an observation sheet of learning implementation. Data were analyzed descriptively, tested for normality with Shapiro-Wilk, followed by the Wilcoxon Signed Rank test because one of the data was not normally distributed, and the increase was calculated through N-gain. The results showed an average pretest score of 41.31 increased to 85.13 in the posttest. The Wilcoxon test showed a significant difference between pre- and post-treatment values ​​(p < 0.001), while the N-gain value of 0.75 was in the high category. Thus, science experiments have proven effective in helping students understand the concept of changes in state of matter in a more concrete, active, and meaningful way.